Reactions of Some Pyrazole-3-Carboxylic Acid Chlorides with Various Anilides - Özer Ilhan, Ilhan; Çadir, Mehmet (Asian Journal of Chemistry, 2012)
1H-pyrazole-3-carboxylic acid chlorides (3) can easily be converted into the corresponding 1H-pyrazole-3-carboxamide (5) by reaction with various anilides. It has been demonstrated that with the variation in reaction conditions, the reaction changes leading to different products. All newly synthesized compounds were characterized by elemental analysis, FT-IR, 1H and 13C NMR spectral data. All compounds were compared with their previous analogues.